On the essential spectra of coupled operators matrix and application. (2nd August 2017) - Belghith, Marwa; Moalla, Nedra; Walha, Ines
Abstract : We define an abstract setting to treat essential spectra of unbounded coupled operator matrix. We prove a well‐posedness result and develop a spectral theory which also allows us to prove an amelioration to many earlier works. We point out that a concrete example from integro‐differential equation fit into this abstract framework involving a general class of regular operator in L 1 spaces.